Effect of superficial air velocity on the fluidized bed drying performance of stingless bee pot-pollen - Luqman, Abdul Halim; Firdaus, Basrawi; Siti Norazualina, Faizal; Ahmmad Shukrie, Md Yudin; Mohd Yusof, Taib (IOP Publishing, 2020)
Stingless bees or “kelulut” also produce pot-pollen apart from honey. The pot-pollen is mixed with honey and bee secretion before stored in cerumen pots. It has high nutritive value and medicinal benefits. Pot-pollens are often neglected by the beekeepers due to difficulty in storing and preserving them due to high moisture content. Hence, fluidized bed dryer is proposed as a suitable method to dry and enable convenient storage and preservation of the pot-pollen. Pot-pollen sample of initial moisture content 30.5 % is dried at three superficial air velocities, 1.0 m/s, 1.5 m/s, and 2.0 m/s for 30 minutes. Fluidized bed drying has managed to decrease the moisture content down to 23.0 %, 20.5%, and 18.5 %, respectively. Higher superficial air velocity lead to higher drying rate in of pot-pollen. Hence, using a fluidized bed dryer to dry stingless bee pot-pollen is a promising method for preserving them. Subsequently, the dried pot-pollen can be easily commercialized in the future.